Dynamic spelling alexia. Issue 4 (April 1986) - Horner, J; Massey, E W
Abstract : A 59-year-old, right-handed, college-educated male examined after stroke presented spelling alexia with relative sparing of writing. He was not aphasic. A striking feature of the alexia was preserved recognition of letters printed in view by the clinician. He was able to read words through letter-by-letter oral spelling when letters were presented in this dynamic fashion. We describe this as a dynamic form of spelling alexia. Head CT scan showed a large left hemisphere posterior lesion infringing on the corpus callosum, and a right hemisphere opercular lesion. We suggest that sparing of the right parietal-occipital cortex may contribute to the remarkable sparing of dynamic letter reading.